A secure arbiter physical unclonable functions (PUFs) for device authentication and identification - Anil Kumar Kurra; Usha Rani Nelakuditi (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
Recent fourth industrial revolution, industry4.0 results in lot of automation of industrial processes and brings intelligence in many home appliances in the form of IoT, enhances M2M / D2D communication where electronic devices play a prominent role. It is very much necessary to ensure security of those devices. To provide reliable authentication and identification of each device and to abort the counterfeiting from the unauthorized foundries Physical Unclonable Functions (PUFs) emerged as a one of the promising cryptographic hardware security solution. PUF is function, mathematically modeled by using uncontrollable/ unavoidable random variances of the fabrication process of the ICs. These variances can generate unpredictable, random responses can be used to overcome the difficulties such as storing the keys in non-volatile memories (NVMs) in the classical cryptography. A wide variety of PUF architectures such as Arbiter PUFs, Ring oscillator PUFs, SRAM PUFs proposed by authors. But due to its design complexity and low cost, Delay based Arbiter PUFs (D-PUFs) are considering to be a one of the security primitives in authentication applications such as low-cost IoT devices for secure key generation. This paper presents a review on the different types of Delay based PUF architectures proposed by the various authors, sources to exhibit the physical disorders in ICs, methods to estimate the Performance metrics and applications of PUF in different domains.